Why Cafés Matter: Rethinking Formal Learning Spaces in Indonesian Higher Education - Dedi Irwan (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2025)
The increasing use of cafés as learning spaces among university students reflects broader changes in how learning is organised beyond formal academic environments. While previous studies have explored informal learning spaces, empirical evidence from developing higher education contexts remains limited. Addressing this gap, the present study investigates why Indonesian university students choose cafés over libraries as learning spaces and examines the perceived learning affordances of both environments. Using a quantitative cross-sectional survey design, data were collected from 355 undergraduate students across diverse academic disciplines and years of study. Descriptive statistics and cross-tabulation analyses with chi-square tests were employed to examine associations between learning space preferences, perceived productivity, collaboration, creativity, motivation, and spatial design. The findings reveal that cafés are strongly associated with collaborative learning, creative idea exchange, and higher learning motivation, whereas libraries remain central for focus-intensive and individual academic tasks. Rather than competing spaces, cafés and libraries function as complementary components within students’ broader learning ecology. Interpreted through Third Place Theory, Affordance Theory, and Learning Ecology, the results highlight a critical mismatch between students’ contemporary learning practices and the design of formal learning spaces. The study concludes by arguing for a rethinking of Indonesian formal learning spaces toward hybrid, multi-zone learning environments that integrate the functional and motivational affordances currently sought by students in informal settings.